ANALISIS PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN TOKOPEDIA DI JAKARTA - Edi Sucipto Tanady; M. Fuad (Jurnal Manajemen, 2020)
This study was conducted to determine whether the brand image and service quality affect the purchase decision of Tokopedia in Jakarta. Brand image is a representation of the overall perception of the brand that is formed from information and experience of the brand. Quality of service is an effort to meet the needs and desires of consumers based on what is expected by consumers. While the purchasing decision is the final decision to make a purchase transaction of a product or service. Respondents from this study are people who have transacted and used the Tokopedia application. This research can be calculated and analyzed multiple linear regression with SPSS 20 software tools. Data collection techniques used are communication techniques by distributing questionnaires to obtain data, whereas in sampling techniques used are non-probability sampling with judgment sampling approach that is sampling which is based on certain criteria or considerations. The results of this study indicate that (1) Brand Image has a positive and significant effect on Purchasing Decisions (2) Service Quality has a positive and significant effect on Purchasing Decisions. Keywords: Brand Image, Service Quality, and Purchase Decisions